Transformation of the fuel and energy complex to ensure Russia’s energy security in the era of sanctions restrictions - V. Ya. Afanasiev; O. I. Bolshakova; A. A. Romantsov (Вестник университета)
Due to the fact that the sanctions regime of Western countries is aimed at destroying Russia’s foreign trade relations and restraining the economic development of Russia, the article considers the increased importance of the main aspects of energy stability and presents a state assessment of Russian Federation energy security in conjunction with energy availability and environmental sustainability using the energy trilemma index. A number of urgent problems that have arisen in the fuel and energy complex as a result of sanctions have been identified. The general scheme of fuel and energy complex transformation is presented and possible ways of solving problems are given. The necessity of carrying out a set of measures for the transformation of the fuel and energy complex, including short- and medium-term measures necessary to ensure the state of energy security and sustainable economic development of Russia is substantiated.